The Structural Relationship Model Predicting Students’ Academic Performance Based on Problem-solving Skills and Intelligence Beliefs with the Mediating Role of Academic Challenge - Mahshid Keyvanlou; Zahra Akhavi Samarein; Shirin Ahmadi (مجله علوم پزشکی صدرا)
Introduction: Investigating students’ academic performance is one of the critical factors in enhancing the quality of school education. The purpose of the present study was to examine the structural relationship model predicting students' academic performance based on problem-solving skills and intelligence beliefs, with the mediating role of academic challenge.Methods: This study was applied in terms of purpose and descriptive in terms of nature and method. The study population included all second-grade high school students enrolled in public schools in Ardabil in 2023. A total of 170 students were selected through a multi-stage cluster random sampling method. They completed questionnaires on academic performance, problem-solving skills, intelligence beliefs, and academic challenges in a group setting at their school. The collected data were analyzed using SmartPLS 4 software.Results: The results of the structural equation model indicated that intelligence beliefs and problem-solving skills had a direct and positive effect on academic performance. Additionally, the indirect effect of intelligence beliefs and problem-solving skills on academic performance was confirmed through the mediation of academic challenge (P<0.001). The model demonstrated a good fit based on the goodness-of-fit indices.Conclusion: In light of the findings and the reciprocal relationships between academic performance, problem-solving skills, intelligence beliefs, and academic challenges, it is recommended that educational practitioners and teachers strengthen students’ problem-solving skills, intelligence beliefs, and academic challenges. This approach is expected to contribute to the improvement of student’s academic performance.